2020
DOI: 10.18421/tem94-35
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Educational Level, Labor Potential and Digital Economy Development in Slovakian, Ukrainian and Russian Experience

Abstract: The purpose of the current paper is to emphasize the role of intellectual labor potential in economy development and digitalization and to explore the features of intellectual work and education as main source and component of the digital information economy. The consequencies of scientific fields representatives' outflow and low renumeration for such three neighboring contries as Slovakia, Ukraine and Russia are observed; their economic indeces are discussed and compared as for more than 10 past years and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The innovative basis of growth requires the labour of qualified specialists. For developing countries' digital economies, the need to strengthen labour potential is an urgent task [18].…”
Section: Study Resultsmentioning
confidence: 99%
“…The innovative basis of growth requires the labour of qualified specialists. For developing countries' digital economies, the need to strengthen labour potential is an urgent task [18].…”
Section: Study Resultsmentioning
confidence: 99%
“…An important factor in the introduction of digital technologies to management is the availability of intellectual labour potential and educated specialists, as well as taking into account the features of intellectual labour [22].…”
Section: Discussionmentioning
confidence: 99%
“…Their study concluded by proposing a new model for transformation in the higher education system based on this division. On the other hand, education is a crucial determinant of the development of the digital economy, as addressed by Miethlich et al [21]. Their study emphasized the role of intellectual labor potential in economic development and digitalization and explored the features of intellectual labor and education as a primary source and component of the digital economy.…”
Section: Educationmentioning
confidence: 99%